HUBUNGAN PENGETAHUAN DAN POLA KONSUMSI JAJANAN DENGAN STATUS GIZI ANAK USIA SEKOLAH DI SD NEGERI 165 PEKANBARU KELURAHAN TABEK GADANG - riamah riamah riamah; Anita Syarifah; awaluddin awaluddin (LPPM Universitas Abdurrab, 2023)
The nutritional status of students is an important indicator in realizing the quality of human resources (HR) who are healthy, intelligent, productive and independent. The purpose of this study was to determine the relationship between knowledge and consumption patterns of snacks with the nutritional status of school-age children at SDN 165 Pekanbaru, Tabek Gadang Village. Data was collected using a questionnaire sheet. The research method used in this study is descriptive correlative with a cross-sectional design with a population of all fifth grade students at SDN 165 Pekanbaru and the sample required is 38 students. Data analysis using univariate and bivariate using chi-suare test. The results of the study with 0.05 with df = 2 and p value 0.000 (p <0.05) meaning that there is a significant relationship between student knowledge and nutritional status in school-age children at SD 165 Pekanbaru. The results of the analysis with 0.05 with df = 2 and p value 0.000 (p <0.05) means that there is a significant relationship between consumption patterns and nutritional status in school-age children at SDN 165 Pekanbaru. As for suggestions in this study, it is hoped that there will be nutritional socialization or nutrition education for school students in choosing snacks that are safe for consumption.